New Ceratorchestes (Acari, Oribatida, Peloppiidae) from Venezuela - Ermilov, Sergey G. (Zootaxa, 2024)
Three new species of Ceratorchestes (Ceratorchestes) (Oribatida, Peloppiidae)—C. (C.) tripartitus sp. nov., C. (C.) duocornutus sp. nov. and C. (C.) truncatus sp. nov.—are described, based on adults collected from leaf litter in northern Venezuela. Ceratorchestes (Paraceratorchestes) melzeri is recorded for the first time from Venezuela. An identification key, distribution and habitat to the known species of Ceratorchestes are provided.